Menyoal Kedudukan dan Otoritas Sunnah dalam Istinbāṭ Al-Aḥkām Ahmadiyah - Hamka Husein Hasibuan; Mhd. Syahnan; Nisful Khoiri; Dhiauddin Tanjung (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article is an attempt to analyze the position and authority of the Sunnah in the Ahmadiyya istinbāṭ al-aḥkām. This departs from the epistemological claim of the Ahmadiyya who explicitly identify themselves as Aḥnāf (followers of the Ḥanafi school), who are essentially ahl ar-ra’y, on the one hand, and at the same time claim to be ahl al-ḥadīs, on the other. This position is methodologically unique and interesting, because it has the potential to create tension between rational reasoning and the authority of hadith texts. This paper is a literature review (library research) by analyzing primary sources of the Ahmadiyya. The results of the study indicate that the sunnah/hadith for the Ahmadiyya is a secondary source of law, by distinguishing between binding sunnah (mulzim li al-hukmi) and non-binding sunnah (gairu mulzim li al-hukmi). However, the authority of the Sunnah is limited to its confirmatory (ta’kid) and explanatory (mubayyin) functions regarding the Qur’an, while its formative (making new laws), takhṣīṣ, and naskh functions are explicitly rejected. This limitation has the effect of narrowing the normative space of the Sunnah. Although theoretically it does not recognize the formative function of the hadith (making new laws), in practice, the Ahmadiyya uses the hadith to create new laws, namely when legitimizing the mahdīth and mujaddiqīyah of Mirza Ghulam Ahmad, even though this is not mentioned in the Qur’an. This “narrow” authority of the Sunnah has consequences for the high authority of the caliph in the practice of istinbāṭ al-ahkām of the Ahmadiyya. Of course, this is a characteristic feature of istinbāṭ al-ahkām, where the caliph has the highest authority as the highest interpreter. This finding also emphasizes the importance of studying Islamic jurisprudence (fiqh) and Islamic jurisprudence (ushul fiqh) in understanding the dynamics of Ahmadiyya thought more comprehensively.